2020
DOI: 10.1186/s12889-020-09927-4
|View full text |Cite
|
Sign up to set email alerts
|

Once is rarely enough: can social prescribing facilitate adherence to non-clinical community and voluntary sector health services? Empirical evidence from Germany

Abstract: Background Non-clinical health interventions provided by the voluntary and community sector can improve patients’ health and well-being and reduce pressure on primary and secondary care, but only if patients adhere to them. This study provides novel insights into the impact of doctor referrals to such services, known as social prescribing, on patients’ adherence to them. Methods Using a negative binomial model, we analysed electronic visitor records from a community health advice and navigation service in Ger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Most evaluations also did not have a control group, which is a continually noted criticism of the evaluations of social prescribing programs (Husk et al, 2019). Further, as noted previously, the participants with poorer mental health and wellbeing were less likely to attend frequently and often lost to follow‐up (Crone et al, 2018; Golubinski et al, 2020; Sumner et al, 2020). Consequently, it is difficult to draw any firm conclusions about the benefit of social prescribing on these groups.…”
Section: Methodological Considerationsmentioning
confidence: 72%
See 1 more Smart Citation
“…Most evaluations also did not have a control group, which is a continually noted criticism of the evaluations of social prescribing programs (Husk et al, 2019). Further, as noted previously, the participants with poorer mental health and wellbeing were less likely to attend frequently and often lost to follow‐up (Crone et al, 2018; Golubinski et al, 2020; Sumner et al, 2020). Consequently, it is difficult to draw any firm conclusions about the benefit of social prescribing on these groups.…”
Section: Methodological Considerationsmentioning
confidence: 72%
“…Similarly, a pilot study of a singing group found no difference in quality of life and an increase in depression symptoms following a 10‐week program (Camic, Williams, & Meeten, 2013). A large study examining social prescription through a health professional compared to self‐referral found that participants that were referred for psychological concerns were less likely to return to the service (Golubinski, Wild, Winter, & Schreyögg, 2020). Another study supported this, finding that participants with higher initial wellbeing were more likely to attend and be engaged (Sumner et al, 2020).…”
Section: Improvement In Mental Health and Wellbeingmentioning
confidence: 99%
“…There is evidence that participating in social prescribing interventions increases patients' sense of wellbeing, through improved confidence and motivation, and reduced social isolation (Hanlon et al, 2019;Hassan et al, 2020;Moffatt et al, 2017). It has also been found that link-worker social prescribing J o u r n a l P r e -p r o o f 20 interventions improve adherence to community and voluntary non-clinical health services (Golubinski et al, 2020). Finally, participation in social prescribing interventions can improve patients' understanding and management of their physical and mental health conditions (Bhatti et al, 2021;Hassan et al, 2020;Moffatt et al, 2017; J. M. Wildman et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…34 Some countries have repurposed existing healthcare staff to administer social prescriptions. The first social prescribing projects in Portugal, 10 Germany, 19 Japan 21 and Canada 35 added these responsibilities to the roles of social workers, allied health professionals, nurses and volunteers. In Spain, social prescriptions are provided directly by primary care physicians, whose ongoing relationships with patients enable them to co-produce appropriately tailored prescriptions.…”
Section: Workforcementioning
confidence: 99%